2012
DOI: 10.1128/iai.00101-12
|View full text |Cite
|
Sign up to set email alerts
|

Coxiella burnetii Alters Cyclic AMP-Dependent Protein Kinase Signaling during Growth in Macrophages

Abstract: ABSTRACTCoxiella burnetiiis the bacterial agent of human Q fever, an acute, flu-like illness that can present as chronic endocarditis in immunocompromised individuals. Following aerosol-mediated transmission,C. burnetii Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 47 publications
0
26
0
1
Order By: Relevance
“…Total Bad levels remained constant throughout the infection time‐course. Akt activity is required for C. burnetii prevention of apoptosis, and is activated between 2 and 6 hpi (Voth and Heinzen, ), while PKA activation is observed from 24 to 96 hpi (Voth and Heinzen, ; MacDonald et al ., ). Densitometry analysis confirmed that the timing of increased Bad phosphorylation corresponds to kinase activation, suggesting Akt is activated first during infection and phosphorylates Bad at Ser136, followed by PKA activation and Bad Ser155 phosphorylation (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Total Bad levels remained constant throughout the infection time‐course. Akt activity is required for C. burnetii prevention of apoptosis, and is activated between 2 and 6 hpi (Voth and Heinzen, ), while PKA activation is observed from 24 to 96 hpi (Voth and Heinzen, ; MacDonald et al ., ). Densitometry analysis confirmed that the timing of increased Bad phosphorylation corresponds to kinase activation, suggesting Akt is activated first during infection and phosphorylates Bad at Ser136, followed by PKA activation and Bad Ser155 phosphorylation (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…We recently demonstrated that primary human alveolar macrophages (hAMs) are a human disease‐relevant platform to investigate C. burnetii ‐regulated signalling required for infection (Graham et al ., ), and PKA is activated by virulent C. burnetii during growth in primary hAMs (MacDonald et al ., ). To determine if virulent C. burnetii modulates PKA‐dependent pro‐survival signalling, we infected primary hAMs with virulent Nine Mile I (NMI) C. burnetii and assessed the impact of PKA inhibition on apoptosis.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies demonstrated the importance of intracellular signalling cascade activation for C. burnetii PV formation and prevention of apoptosis (Voth and Heinzen, ; Hussain et al ., ; Hussain and Voth, ; MacDonald et al ., ). The organism inhibits apoptosis by activating kinases such as Akt and Erk1/2, promoting an anti‐apoptotic transcriptional programme and preventing cytochrome c release from mitochondria (Luhrmann and Roy, ; Voth et al ., ; Luhrmann et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…To better understand the importance of autophagy in vivo, we used two models of C. burnetii-macrophage interactions. First, we used macrophage-like THP-1 cells, an established in vitro model of C. burnetii-host cell interactions (32)(33)(34). PV in THP-1 cells interacted with autophagosomes from 24 to 96 hpi, suggesting that these interactions occur throughout intracellular growth in macrophages.…”
Section: Discussionmentioning
confidence: 99%